Cop in the hood: my year policing Baltimore's eastern district - Moskos, Peter (Princeton University Press, 2008)
The departed -- Back to school : the police academy -- New Jack : learning to do drugs -- The corner : life on the street -- 911 is a joke -- Under arrest : discretion in the ghetto -- Prohibition : Al Capone's revenge -- Epilogue: School daze